Ecological impacts of invasive plants on pollinators : studies on an individual, species and community scale - Tiedeken, Erin Jo (Trinity College (Dublin, Ireland). Department of Botany, 2015)
Pollination is a critical ecosystem service yet pollinators are experiencing worldwide declines. Although invasive alien species are cited as a major driver of pollinator declines, little is known about how pollinators are affected by plant invasion. My thesis used invasive Rhododendron ponticum L. as a model system to better understand how invasive alien plant species impact native pollinators on a variety of scales, from individuals, to species, to entire pollinator communities. Furthermore, the nectar of invasive R. ponticunn contains grayanotoxins, plant secondary compounds usually associated with defence against herbivores. This paradoxical floral trait allowed me to simultaneously Investigate how novel nectar secondary compounds from an invasive plant affect the health and well being of native, non-adapted pollinators, and to consider how plant traits modulate the impacts of invasion for pollinators.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin